Association between leukocyte telomere length and specific antibody levels after vaccination against tick-borne encephalitis - N. S. Yudin; V. A. Belyavskaya; V. N. Maksimov; D. E. Ivanoshchuk; P. S. Orlov; M. I. Voevoda (Вавиловский журнал генетики и селекции)
The primary objective of personalized vaccination is to induce an efficient immune defense while avoiding excessive immunization. Hence, it necessitates the development of methods for predicting the magnitude of the immune response prior to vaccination. Telomere length can be considered as a promising prognostic parameter for assessing the immune response to vaccination. The aim of the work was to analyze the possible association between leukocyte telomere length and specific antibody levels after vaccination against tick-borne encephalitis. The study included 55 men and 40 women who had not previously been vaccinated against tick-borne encephalitis and had no contacts with ticks. Vaccination was carried out with the EnceVir vaccine. One month after vaccination, the level of specific IgG antibodies against tick-borne encephalitis virus was analyzed using the VektoVKE-IgG-strip test system and leukocyte telomere length was measured using real-time quantitative PCR. According to the intensity of vaccine-elicited immune responses, patients were divided into three groups: unresponsive (IgG level 0–100 IU/ml), slightly responsive (IgG level 101–200 IU/ml) and highly responsive (IgG level above 200 IU/ml). The telomere length, at least at trend level (p < 0.1), correlated with the response to vaccination as well as age, educational level and the presence of emotional stress. Using a general linear model, an association between telomere length and immune response to vaccination against tick-borne encephalitis at trend level (p < 0.1) was found only in women. Using a pairwise comparison, it was found that telomere length was significantly higher in highly responsive women than in unresponsive women. Hence, an association between leukocyte telomere length and specific antibody levels after vaccination against tick-borne encephalitis was identified in women. Therefore, peripheral blood leukocyte telomere length can be considered as a promising marker for predicting lymphocyte proliferative responses and the magnitude of vaccine-elicited cellular immune responses.